SU‐E‐I‐16: Scan Length Dependency of the Radial Dose Distribution in a Long Polyethylene Cylinder - Bakalyar, D; Feng, W; McKenney, S (Medical physics (Lancaster), 2015)
Purpose: The area‐averaged dose in the central plane of a long cylinder following a CT scan depends upon the radial dose distribution and the length of the scan. The ICRU/TG200 phantom, a polyethylene cylinder 30 cm in diameter and 60 cm long, was the subject of this study. The purpose was to develop an analytic function that could determine the dose for a scan length L at any point in the central plane of this phantom. Methods: Monte Carlo calculations were performed on a simulated ICRU/TG200 phantom under conditions of cylindrically symmetric conditions of irradiation. Thus, the radial dose distribution function must be an even function that accounts for two competing effects: The direct beam makes its weakest contribution at the center while the scatter begins abruptly at the outer radius and grows as the center is approached. The scatter contribution also increases with scan length with the increase approaching its limiting value at the periphery faster than along the central axis. An analytic function was developed that fit the data and possessed these features. Results: Symmetry and continuity dictate a local extremum at the center which is a minimum for the ICRU/TG200 phantom. The relative depth of the minimum decreases as the scan length grows and an absolute maximum can occur between the center and outer edge of the cylinders. As the scan length grows, the relative dip in the center decreases so that for very long scan lengths, the dose profile is relatively flat. Conclusion: An analytic function characterizes the radial and scan length dependency of dose for long cylindrical phantoms. The function can be integrated with the results expressed in closed form. One use for this is to help determine average dose distribution over the central cylinder plane for any scan length.